Clinical Applications of Oliceridine: Current Research Status, Progress, and Outlook - Shizhu Lin (Asploro Journal of Biomedical and Clinical Case Reports, 2026)
Oliceridine (TRV-130) is the first G protein-biased μ-opioid receptor (MOR) agonist approved by the U.S. FDA for marketing; it was approved in 2020 for the treatment of moderate-to-severe acute pain in adults. Unlike traditional opioids, oliceridine achieves a dissociation between analgesic effects and opioid-related adverse reactions by preferentially activating G protein signaling pathways and reducing β-arrestin 2 recruitment. In recent years, with the approval of oliceridine in China and the conduct of multiple clinical studies, evidence supporting its use in areas such as postoperative pain management, pain-free endoscopy, and outpatient surgery has continued to accumulate. Based on existing clinical evidence, this article provides a systematic review of the pharmacological characteristics, clinical research progress, and key unresolved issues regarding oliceridine, with the aim of offering guidance for rational clinical use and future research.